JALAN PANJANG PENANGANAN KORUPSI DI INDONESIA - Subhan Sofhian (JENTRE, 2021)
In today, corruption is not an alien thing in society, it is even an inseparable part of life in its various forms. Corruption is often done whether we realize it or not and it is done individually or in groups.Conceptually, corruption is not an action that is only carried out by the government, but can also be carried out by all groups and strata of society, both consciously and unconsciously.In the most common cases, the corruption known to the public is corruption committed by public officials. This is in line with the loss of state money which is represented as public money, causing losses to the survival of the community.Historically, corruption occurred since the interests of individuals and groups exist in an organization. These interests bring new policies in the midst of existing programs and activities, giving rise to motivation to enrich one particular party even massively, coordinatively and periodically.This study limits the explanation of corruption in the three eras or orders known especially in Indonesia, namely the orde lama, order baru and orde reformasi. The characteristics and characteristics of each order carry different motivations and forms in the context of violations of the criminal act of corruption. This study was conducted using the on-desk literacy study method. This means that this study is based on printed and electronic data and information in the form of academic texts, journals, books and / or supporting scientific studies.